Are the dinosauromorph femora from the Upper Triassic of Hayden Quarry (New Mexico) three stages in a growth series of a single taxon? - MÜLLER,RODRIGO T. (2017)
ABSTRACT The lagerpetid Dromomeron romeri and the theropod Tawa hallae are two dinosauromorphs from the Norian (Upper Triassic) of the Chinle Formation, situated in New Mexico, USA. However, a recent study suggests the inclusion of the holotype of D. romeri (GR 218) and paratype (GR 155) and referred (GR 235) specimens of T. hallae in an ontogenetic series of a single species. The specimens GR 218 and GR 155 include just an isolated femur, while GR235 includes femora, pelvis and tail. The inclusion of the specimens in an unique ontogenetic series relies on the putative immature condition and plastic deformation of the specimen GR 218. However, as observed here, the disparity between the femora of D. romeri and T. hallae is considerably higher than those expected from the ontogenetic variance in dinosauromorphs. In addition, D. romeri shares an unique suite of traits with Dromomeron gigas, a species known from a mature specimen. Therefore, the high disparity between D. romeri and T. hallae, lack of traits shared solely between the three femora, and a suite of traits shared between D. romeri and D. gigas, precludes the inclusion of the three femora from Hayden Quarry in a growth series of a single taxon.